Legislative provision of space tourism - Mekchovich, E. S.; Pererva, P. G. (My University, 2023)
An important aspect of space tourism, in addition to infrastructure, is the proper licensing and authorization of space facilities and space tourists. The government of a country where space tourism is practiced should take the initiative to provide adequate training to potential tourists, and awareness programs should be conducted.
Законодавче забезпечення космічного туризму
Keywords: space tourism; business; travel; legal support